The Effect of Providing Goat Manure Bokashi Fertilizer on the Growth and Yield of Pakcoy (Brassica rapa L.) Plants in Aimas Village, Sorong Regency - Wanane, Jhon Calvin Wilson; Soekamto, Mira Herawati; Sangadji, Ismail Munadi (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
Increasing the productivity of pak choy plants (Brassica rapa L.) can be done by providing organic goat dung bokashi fertilizer. This research aims to see the effect of providing goat dung bokashi fertilizer and the best dose on the growth of pak choy mustard greens. The method in this research was an experiment designed using a randomized block design with treatment doses of goat manure bokashi fertilizer at various levels, namely K0 (Control) = No treatment K1 (5 tons/ha = 1 kg/plot), K2 (10 tons/ha = 2 kg/plot), K3 (15 tons/ha = 3 kg/plot), K4 (20 tons/ha = 4 kg/plot). Analysis of the observation results was carried out using ANOVA followed by the BNJ test at the 5% level. The results of the research showed that goat manure bokashi treatment had a significant to very significant effect on the growth of plant height, number of leaves, leaf area and wet stover weight of pak choy plants with the best growth at treatment doses of 3 kg/plot (K3) and 4 kg/plot ( K4) had the best growth with an average plant height of 28.35 cm and 27.77 cm, number of leaves 22.80 and 22.27, leaf area of 154.37 cm2 and 163.10 cm2 and wet stover weight of 283.94 grams and 234.42 grams, while the lowest growth was in no treatment or control with an average plant height of 23.96 cm, number of leaves 19.93, leaf area 99.43 cm2 and wet stover weight 138.18 grams. LoA, Kor